(untitled) (Brazilian Journal of Health Research, 2023)
Introduction: Pancreatic ascites results from duct rupture or pancreatic pseudocyst. Chronic pancreatitis is the most common cause, occurring in up to 4% of cases and is managed conservatively, reserving endoscopic and surgical treatments for refractory cases. Case presentation: Male patient, 54 years old, smoker, alcoholic, with recurrent abdominal pain, later history of abdominal trauma with worsening pain in the upper abdomen, irradiation to the back and large volume ascites. Serum laboratory tests with increased inflammatory tests, amylase 1.278 U/l and lipase 915 U/I. Ascitic fluid: amylase 14.403 U/l. Imaging exams confirmed chronic pancreatitis and a pseudocyst communicating with a fistulous tract that drained into voluminous ascites. Initially conducted on enteral nutritional support with an oligomeric diet and correction of hydroelectrolytic disorders, after 15 days he maintained ascites, which was considered a failure of clinical treatment and required passage of a pancreatic prosthesis by endoscopic retrograde cholangiopancretography and resolution of the condition. Conclusion: Pancreatic ascites is a rare complication of chronic pancreatitis with high morbidity and mortality. The diagnosis depends on suspicion in case of abdominal pain that precedes ascites, which is confirmed with the measurement of amylase in the ascitic fluid, showing a result above the serum value or above 1000 U/l. Clinical treatment consists of enteral nutrition with an oligomeric diet, if there is no complete resolution of ascites, endoscopic treatment with passage of a pancreatic prosthesis or surgical treatment is indicated. Multidisciplinary follow-up with clinicians, endoscopists, radiologists and surgeons are essential to avoid unfavorable outcomes.